The efficacy and safety of anlotinib combined with platinum-etoposide chemotherapy as first-line treatment for extensive-stage small cell lung cancer: A Chinese multicenter real-world study - Zheng, Hao-Ran; Jiang, Ai-Min; Gao, Huan; Liu, Na; Zheng, Xiao-Qiang; Fu, Xiao; Ruan, Zhi-Ping; Tian, Tao; Liang, Xuan; Yao, Yu (Frontiers in Oncology, 2022)
Background Anlotinib, an antiangiogenic multi-target tyrosine kinase inhibitor (TKI), was approved as the third-line and above treatment for small cell lung cancer (SCLC) in China. Some small sample size clinical trials have shown the favorable efficacy of anlotinib combined with platinum-etoposide chemotherapy as the first-line treatment for extensive-stage SCLC (ES-SCLC). This research aimed to explore the real-world efficacy and safety of anlotinib combined with platinum-etoposide chemotherapy as the first-line treatment. Methods Pathologically confirmed ES-SCLC patients receiving anlotinib plus platinum-etoposide chemotherapy as the first-line treatment were enrolled in this retrospective study. The primary endpoint of this study was progression-free survival (PFS), and secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse reactions. Results In total, 58 patients were included in this study. The median PFS was 6.0 months [95% confidence interval (CI): 3.5-8.5], and the median OS was 10.5 months (95%CI 8.7-12.3). Thirty-four patients achieved partial response (PR), 18 patients achieved stable disease (SD), and 6 patients achieved progressive disease (PD). The ORR and DCR were 58.6% and 89.6%. The main treatment-related adverse reactions were generally tolerated. The most common adverse reaction was myelosuppression (44.8%), followed by hypertension (41.4%), fatigue (34.5%), gastrointestinal reaction (32.7%), hand-foot syndrome (24.1%), and so on. Multivariate analysis showed that post-medication hand-foot syndrome [PFS 8.5 vs. 5.5 months, Hazards Ratio (HR)=0.23, 95%CI 0.07-0.72, P =0.012] was the independent predictor of PFS, and hypertension (OS 15.9 vs. 8.3 months, HR=0.18, 95%CI 0.05-0.58, P =0.005) was the independent predictor of OS. Conclusion Anlotinib combined with platinum-etoposide chemotherapy as the first-line treatment for ES-SCLC appears to be effective and well-tolerated in the real-world. Patients with post-medication hypertension and hand-foot syndrome may confer superior prognosis. Further investigations are needed by prospective studies with larger sample size.